Ozone disc nucleolysis as an alternative to open disc surgery for slip disc (Bangladesh Medical Journal, 2014)
Back pain associated with herniated disks has become an important and increasingly general health problem, both in Bangladesh and across the world. After all methods of conservative treatment have been exhausted, nucleolysis may be a minimally invasive alternative to surgery. In nucleolysis, chondrolytic substances, or other substances which reduce the pressure within the disk by other means, are injected into the nucleus pulposus under CT scan or fluroscopic guidance. Among various substances, which have been employed for nucleolysis, an ozone-oxygen mixture appears to be very promising. The water-binding capacity of ozone results in a reduction of pain. Moreover, it has an anti-inflammatory effect and results in an increase in perfusion to the affected area. Ozone is converted into pure oxygen in the body and has a low allergic potential. Recent minimally invasive therapeutic methods such as percutaneous nucleotomy or laser treatment have not been shown to be superior when compared with ozone nucleolysis. DOI: http://dx.doi.org/10.3329/bmj.v43i1.21380 Bangladesh Med J. 2014 January; 43 (1): 51-55